PROPERTIES OF ASPHALT CONCRETE WITH A FIBROUS POLYMER ADDITIVES - and; and (Municipal economy of cities. Series: «Economy science», 2013)
The results of experimental studies of the physical and mechanical properties of asphalt concrete types with different particle size fibrous polymeric additive.